Effects of Acupuncture on 1-Chloro-2, 4-dinitrochlorobenzene-Induced Atopic Dermatitis. (7th August 2013) - Park, Ji-Yeun; Park, Hi-Joon; Choi, You Yeon; Kim, Mi Hye; Kim, Seung-Nam; Yang, Woong Mo
Abstract : Though the effects of acupuncture in atopic dermatitis have been proven in clinical studies, its mechanism remains unclear. In this study, we investigate the effectiveness and mechanism of action for acupuncture treatment on the LI11 meridian point for treatment of allergic contact dermatitis. BALB/c mice received 1-chloro-2, 4-dinitrobenzene (DNCB) application to induce skin inflammation. Acupuncture treatment on LI11 significantly inhibited cutaneous hyperplasia, serum IgE levels, and expression of proinflammatory cytokine (IL-4, IL-8, and TNF- α ) mRNA and NF- κ B, ERK1/2, JNK, and p38 proteins. Acupuncture treatment of local points also inhibited cutaneous hyperplasia and serum IgE levels; however, it was not effective in regulating proinflammatory cytokines and proteins. In addition, LI11 treatment is more effective at reducing serum IgE levels and pro-inflammatory cytokines and proteins than local point treatment. These results suggest that acupuncture treatment is effective in alleviating allergic contact dermatitis by reducing pro-inflammatory cytokines and proteins.